Retrospective analysis of primary pulmonary lymphoma cases from Polish Lymphoma Research Group centers reveals associations between initial symptoms and outcomes - Agnieszka Giza; Paulina Dumnicka; Elżbieta Kalicińska; Joanna Romejko-Jarosińska; Joanna Drozd-Sokołowska; Aleksander Kania; Dagmara Zimowska-Curyło; Wanda Knopińska-Posłuszny; Grażyna Siewior; Renata Guzicka-Kazimierczak; Magdalena Witkowska; Marta Morawska; et al. (Scientific Reports)
Abstract Primary pulmonary lymphoma (PPL) is a rare extranodal lymphoma, accounting for only 0.4% of all lymphomas. We conducted a retrospective analysis of 78 patients with PPL treated at 15 tertiary care hematooncology centers in Poland. The study revealed a high incidence of aggressive B-cell lymphoma (42%), although this may reflect the specificity of participating centers. A high prevalence of pleural effusion and dyspnea at the time of diagnosis was found to be associated with worse overall survival in all PPL patients. Dyspnea and bilateral lung lesions at presentation were associated with a lack of complete remission, while the presence of cough was associated with shorter time to disease progression or relapse. Although the progression-free survival did not differ significantly between patients with low- versus high-grade B-cell PPLs, those with indolent PPLs exhibited superior overall survival. To the best of our knowledge, this study is the first multicenter retrospective analysis of PPL in Central Europe involving such a large cohort of patients.